2022
DOI: 10.3390/ijerph19042482
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Positive Orientation and Control of Anger, Anxiety and Depression in Nursing Students in Poland, Spain and Slovakia during the COVID-19 Pandemic

Abstract: (1) This study analysed the relationship between positive orientation and subjective control of anger, anxiety and depression in nursing students in Poland, Spain and Slovakia during the pandemic. (2) The survey was carried out by the diagnostic survey method in a group of 756 nursing students in Poland, Spain and Slovakia. The empirical data were gathered using an original survey questionnaire, the Positive Orientation Scale and the Courtauld Emotional Control Scale. (3) It was shown that the positive orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 69 publications
2
11
1
Order By: Relevance
“…Alessandri et al argue that positive orientation is a multidimensional construct of a higher order, integrating three components, which—according to literature reports—are associated with well-being and success in many areas of human life, such as health, learning achievements and work performance [ 56 ]. The mean positive orientation score, as measured in this study, was 26.87 (SD = 5.90) points, which was much lower than in the normalization sample (M = 29.19; SD = 4.55) [ 16 ], as well as in an international study among students in Spain (M = 29.20; SD = 5.18) and Slovakia (M = 29.22; SD = 5.49) [ 57 ]. The findings of this study of positive orientation showed its level to be low in more than half of the students, which may result in unfavorable self-assessment, low life satisfaction and poor assessment of the chances of achieving personal goals, as well as negative perception of the capacity to cope with difficulties and adversities.…”
Section: Discussionmentioning
confidence: 69%
“…Alessandri et al argue that positive orientation is a multidimensional construct of a higher order, integrating three components, which—according to literature reports—are associated with well-being and success in many areas of human life, such as health, learning achievements and work performance [ 56 ]. The mean positive orientation score, as measured in this study, was 26.87 (SD = 5.90) points, which was much lower than in the normalization sample (M = 29.19; SD = 4.55) [ 16 ], as well as in an international study among students in Spain (M = 29.20; SD = 5.18) and Slovakia (M = 29.22; SD = 5.49) [ 57 ]. The findings of this study of positive orientation showed its level to be low in more than half of the students, which may result in unfavorable self-assessment, low life satisfaction and poor assessment of the chances of achieving personal goals, as well as negative perception of the capacity to cope with difficulties and adversities.…”
Section: Discussionmentioning
confidence: 69%
“…There is a lack of international research showing how and to what extent life satisfaction translates into the social and emotional functioning of nursing students during a pandemic. In contrast, some variables (e.g., related to social isolation) have been previously studied in the context of pandemics and have been reported in the global literature [28][29][30]. This is confirmed by the findings of Eweid et al, which showed that the most stressful factors for nursing students during the clinical classes during the COVID-19 pandemic were associated with a risk of infection and virus transmission to a relative.…”
Section: Introductionmentioning
confidence: 72%
“…This study is part of an international research project executed within the framework of one of the researcher’s (E.K.) scientific internship programme [ 28 , 32 ]. This project was given a favourable opinion (No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations